Teologi Sebagai Landasan Bagi Gereja Dalam Mengembangkan Pendidikan Agama Kristen - Hepni Putri S; Asnawati Saogo; Sandra R Tapilaha (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The church is a fellowship of saints, called by God to fulfill His mission of teaching sound doctrine to believers in accordance with the Bible. Christian education (PAK) is one of the teaching tasks in the church. This must be done continuously to meet the needs of the faithful. To remain relevant, the church must develop by considering the influence of modern developments that befall the church. In addition, the congregation has shown changes in behavior and lifestyle that are always up-to-date. In addition, the church also encounters teachings that deviate from the Bible and the correct theological foundation. In the development of PAK, the church cannot be separated from theology which is the content of PAK itself. The teaching practiced in the church focuses on God and His work. To understand this, a theology is needed that makes it easy to explain what God's will is for His people. By making theology the basis for the development of biblical PAK, the church grows into a productive congregation that produces more mature congregations who can live out their faith in their daily lives. This article is written using a qualitative descriptive method through literature research. The conclusion of this article is that the church must understand that PAK is a very important mission of the church and needs to be further developed. PAK is part of the church's theological work, so the church must develop PAK based on theology, and theology becomes the basis for the development of PAK in the church.